2012
DOI: 10.1074/jbc.m112.355412
|View full text |Cite
|
Sign up to set email alerts
|

Dual-specificity Tyrosine Phosphorylation-regulated Kinase 1A (Dyrk1A) Modulates Serine/Arginine-rich Protein 55 (SRp55)-promoted Tau Exon 10 Inclusion

Abstract: Background: Dysregulation of the alternative splicing of Tau exon 10 causes several types of neurodegenerative diseases. Results: SRp55 promotes Tau exon 10 inclusion. Dyrk1A interacts with SRp55, mainly phosphorylates its proline-rich domain and inhibits its ability to promote Tau exon 10 inclusion. Conclusion: Dyrk1A suppresses SRp55-promoted Tau exon 10 inclusion. Significance: Up-regulation of Dyrk1A disrupts the alternative splicing of Tau exon 10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 45 publications
1
66
0
1
Order By: Relevance
“…First, we studied the domain-specific role of SRSF6 in CRC. Because SRSF6 contains two RNA recognition motifs at the N terminus and RS domains at the C terminus,22 we generated various deletion mutants of SRSF6 (figure 7A,B). When transfecting these mutants into SW620 cells with SRSF6 shRNA, we found that RRM1 deletion mutant could significantly decrease ZO-1 exon23 inclusion transcript similar to SRSF6 full-length expression vector, but the RRM2 deletion or RRM1&RRM2 deletion mutant failed to inhibit ZO-1 exon23 inclusion (figure 7C).…”
Section: Resultsmentioning
confidence: 99%
“…First, we studied the domain-specific role of SRSF6 in CRC. Because SRSF6 contains two RNA recognition motifs at the N terminus and RS domains at the C terminus,22 we generated various deletion mutants of SRSF6 (figure 7A,B). When transfecting these mutants into SW620 cells with SRSF6 shRNA, we found that RRM1 deletion mutant could significantly decrease ZO-1 exon23 inclusion transcript similar to SRSF6 full-length expression vector, but the RRM2 deletion or RRM1&RRM2 deletion mutant failed to inhibit ZO-1 exon23 inclusion (figure 7C).…”
Section: Resultsmentioning
confidence: 99%
“…The SR splicing factor SRSF6 may regulate the AS of HTT through the binding to the 5′ end of mutant HTT mRNA, suggesting a role for this protein in the generation of these transcript isoforms and in the pathogenesis of HD . SRSF6 also regulates the AS of the microtubule‐associated protein tau ( MAPT ) gene, resulting in increased expression of the 4R/3R (four‐ or three‐microtubule‐binding repeats) tau isoform ratio in neuroblastoma cells . Interestingly, the 4R/3R tau ratio is significantly increased in the cortex of HD patients and confers a gain of toxicity in HD pathogenesis .…”
Section: Connections Between Prp40 Proteins and Human Diseasementioning
confidence: 99%
“…Upregulation of Dyrk1A, a tau kinase encoded by a gene located on Down syndrome critical region, suppresses tau exon 10 inclusion, resulting in an increased 3R-tau expression. Therefore, overexpression of Dyrk1A in Down syndrome due to increased gene dosage increases 3R-tau expression, and appears to contribute to earlier onset of tau pathology in this disease [57, 106, 118]. …”
Section: Etiopathogenesis Of Neurofibrillary Degenerationmentioning
confidence: 99%